“Tumour sink effect” on the diagnostic or posttreatment radioiodine scan due to sequestration into large-volume functioning metastasis of differentiated thyroid carcinoma influencing uptake in smaller metastatic sites or remnant thyroid tissue: An uncommon but possible phenomenon in thyroid cancer practice - Basu, Sandip; Ranade, Rohit; Abhyankar, Amit (World Journal of Nuclear Medicine, 2020)
Two patients of differentiated thyroid carcinoma are illustrated demonstrating “sink effect” in posttherapeutic and diagnostic radioiodine (I-131) study: (a) in the first case, it masked the other small-volume metastatic sites (pulmonary and paratracheal nodes) in the posttreatment scan, which were clarified following metastatectomy of the large-volume skeletal metastatic lesion, and (b) in the second, interestingly, it masked the remnant thyroid uptake in the first postoperative diagnostic radioiodine study. In both the situations, large-volume highly functioning skeletal metastasis was the cause for the observed “sink effect” and is presented as learning illustrations to the attending physicians. Although uncommon, this is a possible phenomenon in thyroid cancer practice.
Keywords: Differentiated thyroid carcinoma; I-131; radioiodine scan; thyroid carcinoma; tumor sink effect